Mengkaji Peluang Jagung Hibrida Nasa-29 Meningkatkan Produksi Jagung di Lahan Kering Kabupaten Kupang - Sitorus, Alfonso; Menge, Dominika (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Sitorus A, Menge D. 2021. Assessing opportunities of Nasa-29 hybrid maizes to increase yield in dryland of Kupang Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 125-133. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Maize is one of the most important staple crops in East Nusa Tenggara (ENT). Maize is widely grown on dryland as food crop or animal feed. However, its productivity at both regency and provincial levels is still lower than the national average. One of the solution to increase maize productivity is using superior varieties such as Nasa-29 hybrid varieties which has high productivity. The purpose of this study was to examine the opportunities of using Nasa-29 hybrid maize to increase maize productivity in ENT. The study was carried out in Oeteta Village, Sulamu District, Kupang Regency. The study was carried out by making a Nasa-29 hybrid demonstration farm (demfarm) on 20 hectares dryland which spread over 5 farmer groups. During the 2019’s Dry Season (DS) demfarm covering an area of 7 hectares and 13 hectares on the 2020’s Wet Season (WS). Growth and production data were collected and analyzed statistically using Least Significant Difference (LSD) test at 5% level to exemine the significance of differences between the treatment means. Data of productivity, costs, and net income were used to calculate the B/C ratio. The results of the study showed that the production of hybrid maize in WS and DS was not significantly different based on the LSD test at the 5% level. Nasa-29 hybrid maize can increase productivity up to 181% compared to the existing condition (2.59 t/ha) which were up to 189% on WS and 176% on DS. The B/C analysis showed that hybrid maize farming system was feasible (B/C ratio value > 1) which were 1.35 on DS and 2.65 on WS. So, it can be concluded that Nasa-29 hybrid maize potentially to increase corn production in ENT.